Effect of uremic toxins on hippocampal cell damage: analysis in vitro and in rat model of chronic kidney disease. Issue 2 (February 2021) - Watanabe, Kimio; Sato, Emiko; Mishima, Eikan; Watanabe, Mayu; Abe, Takaaki; Takahashi, Nobuyuki; Nakayama, Masaaki
Abstract: One third of the patients with chronic kidney disease (CKD) develop cognitive impairment, which is also an independent risk factor for mortality. However, the concise mechanism of cerebro-renal interaction has not been clarified. The present study examines the effects of uremic toxins on neuronal cells and analyzes the pathological condition of the brain using mouse hippocampal neuronal HT-22 cells and adenine-induced CKD model rats. Among the uremic toxins analyzed, indoxyl sulfate, indole, 3-indoleacetate, and methylglyoxal significantly decreased viability and glutathione level in HT-22 cells. The mixture of these uremic toxins also decreased viability and glutathione level at a lower dose. Adenine-induced CKD rat showed marked renal damage, increased urinary oxidative stress markers, and increased numbers of pyknotic neuronal cells in hippocampus. CKD rats with damaged hippocampus demonstrated poor learning process when tested using the Morris water maze test. Our results suggest that uremic toxins have a toxic effect on hippocampal neuronal cells and uremic CKD rats shows pyknosis in hippocampus. Abstract : Cerebro-renal interaction; Cognitive impairment; Chronic kidney disease; Uremic toxins.